ESSENTIAL FEATURES OF MODERN PARLIAMENTARISM - Surai I.H.; Honchar V.V. (Pressing Problems of Public Administration, 2016)
The article shows the understanding of the modern parliamentarism by a number of researchers. Thearticle focuses on identifying and reasoning of the essential features of modern parliamentarism. It isproved that the main features of modern parliamentarism are the interaction of civil society and the state;the principle of representation; the supremacy of the parliament; democracy.